2016
DOI: 10.20537/vm160102
|View full text |Cite
|
Sign up to set email alerts
|

On the spectral set of a linear discrete system with stable Lyapunov exponents

Abstract: All Russian mathematical portal I. N. Banshchikova, S. N. Popova, On the spectral set of a linear discrete system with stable Lyapunov exponents, Vestn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The perturbation R(•) = R(t) t∈Z ⊂ M n (K) will be called a multiplicative perturbation of system (2). Definition 7 (see [44]): A multiplicative perturbation R(•) is called admissible if the sequence R(t) t∈Z is a Lyapunov sequence.…”
Section: Local Lyapunov Reducibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The perturbation R(•) = R(t) t∈Z ⊂ M n (K) will be called a multiplicative perturbation of system (2). Definition 7 (see [44]): A multiplicative perturbation R(•) is called admissible if the sequence R(t) t∈Z is a Lyapunov sequence.…”
Section: Local Lyapunov Reducibilitymentioning
confidence: 99%
“…Let us notice that all time-invariant or all periodic systems are regular. Definition 14 (see [44]): The Lyapunov spectrum of system ( 2) is called stable if for any ε > 0 there exists…”
Section: Local Assignability Of the Lyapunov Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that in order for the stability of the Lyapunov spectrum of system (2) to hold, it is necessary and sufficient that this system can be reduced to a block-triangular form by some Lyapunov transformation, such that the blocks are integrally separated [9] and for each block, the upper and lower central exponents [7,8,22] coincide. Similar conditions hold for linear discrete-time systems [3]. It is important to notice that, in general these conditions are unverifiable, since for their application we must transform system (2) (or system (4)) into some special form by Lyapunov transformation, but the algorithms to construct this transformation are unknown.…”
Section: Introductionmentioning
confidence: 95%
“…This property can be called the openness of the Lyapunov spectrum of system (2) (or system (4)). Some results on the openness for continuous-time systems were obtained in [20] and for discrete-time systems in [3].…”
Section: Introductionmentioning
confidence: 99%